2000
DOI: 10.1159/000047316
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m Sestamibi/Tetrofosmin Myocardial Perfusion Scanning in Cardiac and Noncardiac Sarcoidosis

Abstract: Left ventricular (LV) and right ventricular (RV) involvement in sarcoidosis must be firmly confirmed to determine patients’ prognosis. We examined whether myocardial perfusion images using technetium-99m single photon emission computed tomography (SPECT) have a diagnostic benefit in the evaluation of biventricular involvement. Sixteen patients with sarcoidosis, aged 21–78 (54 ± 12) years old, 5 males and 11 females, complicated with cardiac disease (cardiac sarcoidosis, n = 6) including tachyarrhythmias of ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 11 publications
(34 reference statements)
0
31
0
3
Order By: Relevance
“…35, 7, 410-415 (2012) 31 In comparing sestamibi SPECT to gallium scintigraphy, Eguchi et al found a greater prevalence of perfusion defects with 99m Tc-sestamibi in patients with CS (21 of 36; 60%) compared with systemic sarcoidosis (19 of 60; 32%) and healthy controls (11 of 150; 7%). 32 Also, 99m Tc-sestamibi detected defects in 4 of 6 patients with known CS, whereas gallium only detected defects in 1 of 6 patients. 32 To assess the activity of the disease and its potential response to systemic steroid therapy, a dual ( 99m Tcsestamibi + 67-gallium) approach might be beneficial.…”
Section: Cardiac Magneticmentioning
confidence: 87%
See 1 more Smart Citation
“…35, 7, 410-415 (2012) 31 In comparing sestamibi SPECT to gallium scintigraphy, Eguchi et al found a greater prevalence of perfusion defects with 99m Tc-sestamibi in patients with CS (21 of 36; 60%) compared with systemic sarcoidosis (19 of 60; 32%) and healthy controls (11 of 150; 7%). 32 Also, 99m Tc-sestamibi detected defects in 4 of 6 patients with known CS, whereas gallium only detected defects in 1 of 6 patients. 32 To assess the activity of the disease and its potential response to systemic steroid therapy, a dual ( 99m Tcsestamibi + 67-gallium) approach might be beneficial.…”
Section: Cardiac Magneticmentioning
confidence: 87%
“…32 Also, 99m Tc-sestamibi detected defects in 4 of 6 patients with known CS, whereas gallium only detected defects in 1 of 6 patients. 32 To assess the activity of the disease and its potential response to systemic steroid therapy, a dual ( 99m Tcsestamibi + 67-gallium) approach might be beneficial. In a study by Nakazawa et al, 33 14 patients with systemic sarcoidosis received a dual scan.…”
Section: Cardiac Magneticmentioning
confidence: 87%
“…It is believed that reverse redistribution in CS is caused by focal reversible microvascular constriction in coronary arterioles around the granulomas (69). According to the results of a few studies, 99m Tc-sestamibi seems to be superior to 201 Tl in detecting reverse distribution (67,70). 67 Ga scintigraphy detects CS during its inflammatory phase, because of accumulation in inflamed areas.…”
Section: Other Radionuclide Imaging Testsmentioning
confidence: 99%
“…Perfusion defects are more common in the RV than the in LV and correlate with atrioventricular block, heart failure, and ventricular tachycardia of RV origin. 55 These defects are frequently reversible, which makes it unlikely that they represent deposition of granulomata or fibrosis. 67 Ga was formerly used in sarcoidosis as a marker of the activity and extent of the disease and for predicting the efficacy of corticosteroids, but it has been largely superseded by serial chest CT and pulmonary function tests.…”
Section: Sarcoid Heart Diseasementioning
confidence: 99%